Prevalence of Urinary Tract Infection among Patients Presenting with Complex Renal Stones at SIUT - Naveed Ahmed Mahar, Harris Hassan Qureshi, Mohsin Mustafa Memon, Ghullam Mustafa Kalhorro, Sara Rasheed Kalwar, Asad Shahzad Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The link between stone formation and urinary tract infections (UTIs) is complicated; research has primarily focused on bacteria’s potential to stimulate the formation of kidney stones. Infective urolithiasis has long been thought to be the result of a urinary tract infection (UTI) caused by bacteria, most commonly belonging to the Proteus genus. Staghorn stone, which is characterised by a massive calculus entirely occupying the renal pelvicalyceal system, is one of the most common kinds of infective lithiasis. This study can serve in identifying the risk of UTI in a patient with complex renal stones, as well as preventing and intervening early. Objective: The goal of this study was to investigate the prevalence of urinary tract infections (UTIs) among patients with complex renal stones who were sent to the Sindh Institute of Urology and Transplantation. Subject and Methods: This cross-sectional study was conducted at Sindh Institute of Urology and Transplantation’s out-patient urology department. This study included a total of 113 patients with complex renal stones. Culture and sensitivity (C/S) tests were performed on a urine sample supplied to the SIUT microbiology lab. The C/S results were gathered and categorized as positive or negative according to the operational criteria. Results: The patients’ average age was 30.83±8.29 years. There were 45 females (39.82 %) and 68 males (60.18 %). A urinary tract infection was observed in 22.12 % (25/113) of patients with complex renal stones. Conclusion: We discovered a high prevalence of urinary tract infection in individuals with complex renal stones, and we propose that patients with acute nephrolithiasis have urine cultures taken and be monitored closely. Empiric therapy should be considered for patients with pyuria, women, or those with clinical characteristics suggestive of infection if sensitivity to diagnose urinary tract infection is to be prioritized because of the potentially serious consequences of under-treatment